Economic freedom, institutional quality, and manufacturing development in African countries - Zewdie Habte Shikur (Journal of Applied Economics, 2024)
The study examines the long and short-run impact of different explanatory variables on manufacturing development the time span from 1996 to 2021. The results indicated that economic freedom, FDI inflows, financial development, political instability, corruption control, government effectiveness, the rule of law, voice and accountability, and regulatory qualities significantly expand industrialization at the 1% level in the short-run, whereas they significantly reduced industrialization at the 1% level in the long run. African manufacturing transformation is significantly and positively determined by income per capita in the long and short run. The study suggests that policy measures must be taken to combat corruption and improve government effectiveness to achieve manufacturing growth. Maintaining a sound individual and whole institutional quality is very crucial for manufacturing development in the short run.
Keywords: 330; financial development; income per capita; population growth; Structural transformation